Аналіз методів управління перерозподілом людських ресурсів в портфелі IT-проєктів - Горбань, І. Ю. (ХНУРЕ, 2024)
The study examines the problems of redistribution of human resources in companies developing network software. Key problems are highlighted: imbalance of resources, neglect of impacts, limited resources, and budget overruns. The method of evaluating projects according to profitability, costs and significance is presented, as well as methods of optimizing the allocation of resources, with an emphasis on linear programming for its efficiency and adaptability. Additional parameters are considered for more detailed analysis, including employee experience and motivation.
Keywords: IT-проєкт; перерозподіл людських ресурсів